Desamerization of Bitter Jam: Biochemical and Sensory Quality - Samira Lagha-Benamrouche; Terkia Benaissa; Rezki Sadoudi (Journal of Food Quality)
This work consists of studying the influence of the desamerization of the mesocarpe on the chemical composition and the sensorial quality of the jam, based on the bitter orange. The results of the various analysis show that desamerization decreases acidity, sugars, protein, and bioactive compound levels (carotenoids, polyphenols, and vitamin C), but desamerized jams still remain an important source of antioxidant compounds with antioxidant potential in the diet. Concerning the sensory analysis of the jams, the results show that the jam desamerized with water presents the same bitterness as the bitter jam and that the salt significantly reduces the bitterness of the jams.